How Dark Is It? From Administration to Faculty - Leary, Tamara; Pardy, Linda (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
Crossing over to the dark side is a popular reference to someone’s decision to leave the supposed “good, pure, and honest” side of something to go to its “bad, evil, and suspicious” side. This idiom is typically used when an administrator moves into a faculty position or vice versa. While there is a plethora of literature on the challenges new scholars face as they enter the academy, less is knownabout the lived experience of moving from being an administrator to faculty member. One might assume the move is straightforward; our own experiences, however, suggest otherwise. This study explores the transition experiences of seven Canadian higher education administrators to faculty positions. Participants shared common experiences and perspectives on the differences between the roles, all of which are exacerbated by the distrust between the two sides. Findings offer further understanding of the nuances and misconceptions held by both parties and propose areas for further research.